Moringa (Moringa oleifera L.): An underutilized and traditionally valued tree holding remarkable potential - Minakshi Jattan (Society for Promotion of Horticulture - Indian Institute of Horticultural Research, 2021)
Moringa (Moringa oleifera L.) commonly known as “drumstick tree” belongs to the family Moringaceae. It is now grown worldwide but its native region is India. It is a fast-growing tree that responds to low inputs and has high regeneration potential after cutting. Its nutritional value and capacity to grow economically in different soils and environmental conditions make it a wonder tree. It is highly nutritious and each part is being utilized in various forms. It is widely cultivated for its young pods, flowers, and leaves for use as traditional herbal medicine and vegetable. It is also used by indigenous people in the tropics and sub-tropics as a source of remedies. The leaves are also used as a source of fodder in many countries of the world as they can sustain green fodder availability around the year without extra efforts. Various parts of this tree are good sources of ascorbic acid, calcium, iron, protein, and antioxidant compounds. Hence, its remarkable properties help to fight nutritional deficiency, human diseases and improve the performance of livestock.